Teaching of Passive and Impersonal Constructions for Chinese-Speakers of Spanish - Lin, Chuan-Chuan (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This study tries to demonstrate how analytical, contrastive and translational methods deepen the interpretations of passive and impersonal forms in Spanish classes for Chinese-speaking students. Passive and impersonal expressions must be based on linguistic structures such as se + V, ser + p.p., se + CInd. + V, verbs in the third person plural and some constructions of verbal periphrasis in direct or indirect ways with the verbs such as quedar, ir, seguir, verse, etc. In Chinese there are 被bèi constructions and other variants of passive values: 為wé, 所suǒ, 給gě, 讓ràng, 由 yóu, 獲huò, 受shòu, 遭zāo, 挨āi, 為wéi...所suǒ, 經jīng, 任rèn y 叫jiào.. The results of this article show that in Chinese and in Spanish the passive and impersonal concepts can be easily and effectively correlated, facilitating the teaching of these constructions.